1985
DOI: 10.1002/hep.1840050409
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Sclerosis and Esophageal Balloon Tamponade in Acute Hemorrhage From Esophagogastric Varices: A Prospective Controlled Randomized Trial

Abstract: A prospective randomized controlled clinical trial was performed in 43 consecutive histologically proved cirrhotic patients with endoscopically proved actively bleeding esophageal varices. Twenty-two were randomly selected to have esophageal tamponade with the Sengstaken-Blakemore tube, and 21 were selected to have endoscopic sclerosis of the esophageal wall. The two groups were similar in demographic, clinical and laboratory data. Bleeding was controlled by the Sengstaken-Blakemore tube in 16 of 22 patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
1
5

Year Published

1986
1986
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(79 citation statements)
references
References 15 publications
2
71
1
5
Order By: Relevance
“…One patient in each group received transjugular previous studies usually observed a short period, such as 8 intrahepatic portosystemic stent shunt after endoscopic or 12 hours. 6,10 In Sung's study, initial control of bleeding treatment failure. Patients requiring vasoconstrictors to con-with emergency EIS was 90%, with a rebleeding rate of 16% trol bleeding were significantly higher in the sclerotherapy within 48 hours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One patient in each group received transjugular previous studies usually observed a short period, such as 8 intrahepatic portosystemic stent shunt after endoscopic or 12 hours. 6,10 In Sung's study, initial control of bleeding treatment failure. Patients requiring vasoconstrictors to con-with emergency EIS was 90%, with a rebleeding rate of 16% trol bleeding were significantly higher in the sclerotherapy within 48 hours.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7] copists. In this study, we compared the short-term effiNevertheless, substantial complications may be associated cacy and safety of banding ligation with injection sclerowith EIS.…”
mentioning
confidence: 99%
“…Randomized trials comparing tamponade to sclerotherapy for EVB show trends or significant benefit for sclerotherapy in initial hemostasis, and all indicate better sustained or definitive hemostasis with sclerotherapy. (6)(7)(8) Thus, tamponade for acute EVB is not better than medical therapy, is less effective than endoscopic therapy, and not uncommonly causes serious and sometimes fatal complications. My view has been that the use of tamponade should be exceedingly rare: e.g., patients with persistent massive known EVB awaiting endoscopy or awaiting transjugular intrahepatic portosystemic shunt after unsuccessful endoscopic intervention.…”
Section: Balloon Tamponadementioning
confidence: 99%
“…Subsequently, the varix becomes organized and eventually disappears [20]. Several drugs have been used as sclerosants including Aethoxysklerol, sodium tetradecyl sulfate, sodium morrhuate, absolute alcohol and ETH [5,6,[21][22][23][24]. In a recent in vivo rat study ETH was found to be superior to Aethoxysklerol because it controlled thrombosis but damaged a smaller area [].…”
Section: Discussionmentioning
confidence: 99%